P636 An unusual cause of gluteal swelling.....congenital rectal duplication cyst. (June 2019) - Mahmood, Qasim; Shabbir, Uzair; Sweeney, Brian; O'Sullivan, Maureen; Yousif, Taha
Abstract : Rectal Duplication (RD) is a very rare phenomenon with only around 100 cases reported.They make up a merely 5% of all intestinal duplication's. Most of the rectal duplication's are located in the retro rectal space. Presenting symptoms include intestinal obstruction, bladder outlet obstruction, dysuria, pelvic pain, mucous or purulent drainage from the rectum or perianal fistula, rectal bleeding from the presence of heterotopic gastric mucosa, constipation and rectal prolapse. RDs are mostly diagnosed with ultrasound and MRI.Treatment of choice in majority of cases is surgical resection. We report a very unusual case of congenital rectal duplication cyst in a newborn.A male baby was delivered by emergency C-section for maternal pre-eclampsia at 39 weeks gestation with birth weight of 3.9 kg.Initial clinical review revealed a large, shiny, dark bluish cystic type lesion on the right buttock.Ultrasound scan of the right buttock showed a large deep cystic lesion measuring 3 cm in diameter in the right gluteal region.At 16 hours of age, the lesion burst through one centimeter opening discharging copious amount of liquid meconium, resulting in the collapse of the swelling.As a result, he received fluid resuscitation, feeds were withheld and he was started on antibiotics for suspected sepsis. MRI pelvis showed a large fluid filled tubular structure in the presacral space displacing both the rectum and bladder.The imaging also showed dilatation of the upper tracts in relation to both kidneys with displaced and distended bladder.Surgery showed rectal duplication cyst sharing a common wall with the rectum, however, there was no direct connection with the rectal lumen and was successfully excised. The biopsies revealed degenerative and necrotic tissue which was unusual.The presence of meconium could be attributed to the presence of a direct connection with the rectal cavity at some stage of the development. The baby was discharged home post surgery and made full recovery without any complications. To our knowledge, this case is the first to present with gluteal swelling and subsequent rupture yielding liquid meconium.